Improving Learning Outcomes of Mathematical Operations Using Whole Numbers Media Card Bridge In Class II students: Meningkatkan Hasil Belajar Matematika Operasi Bilangan Cacah Menggunakan Media Kartu Bridge Pada siswa Kelas II - Zainidar (International Journal of Technology Vocational Education and Training, 2020)
This study aims to determine the effect of using bridge card media to improve mathematics learning outcomes on the subject of addition and subtraction of whole numbers in class IIb of SD Negeri 20 Sitiung. This type of research is a classroom action research conducted in 3 cycles, each of which consists of planning, action, observation and reflection stages. The results of the study: There was an increase in students' skills in answering addition and subtraction questions which included the following aspects: (a) Students who actively answered teacher questions at the beginning of the cycle were 57% and at the end of 90%, (b) Students who dared to do questions on the written board at the beginning of the cycle by 48% and at the end of the cycle by 85%, (c) Students who are active in learning at the beginning of the cycle are 69% and at the end of the cycle are 80%, (d) Students who actively do homework at the beginning cycle of 53% and at the end of the cycle by 95%, (e) Students who actively use bridge card media at the beginning of the cycle are 57% and at the end of the cycle are 95%. From this research, it was concluded that the use of the bridge card game can improve mathematics learning outcomes and the activities of class IIb students of SD Negeri 20 Sitiung on the subject of addition and subtraction of whole numbers.